2010
DOI: 10.1152/ajpcell.00398.2009
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of hypoxia on osteochondrogenic potential of human adipose-derived stem cells

Abstract: Guicheux J. Differential effects of hypoxia on osteochondrogenic potential of human adipose-derived stem cells. Am J Physiol Cell Physiol 298: C355-C364, 2010. First published November 25, 2009 doi:10.1152/ajpcell.00398.2009.-Human adipose tissue-derived stem cells (hATSC) have been contemplated as reparative cells for cartilage engineering. Chondrogenic differentiation of hATSC can be induced by an enriched culture medium and a three-dimensional environment. Given that bone is vascularized and cartilage is n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
108
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 127 publications
(115 citation statements)
references
References 44 publications
4
108
1
2
Order By: Relevance
“…Pellets were cultured for 21 days in FCS-free DMEM supplemented with 10 mg/ml of bovine insulin, 50 mM of ascorbic acid, 10 À8 M of dexamethasone and 10 ng/ml of TGF-b1, as detailed elsewhere. 27 To induce calcification, pellets were then cultured in a-MEM containing 5% FCS, 10 mg/ml of insulin, 10 À8 M 1,25 (OH) 2 VD 3 and 5 mM b-GP. Pellets were finally treated on day 24 with 1 ng/ml of TNF-a and 0.1 ng/ml of IL-1b for 2 days for PCR analysis or 7 days to assess TNAP activity.…”
Section: Cell Culturesmentioning
confidence: 99%
“…Pellets were cultured for 21 days in FCS-free DMEM supplemented with 10 mg/ml of bovine insulin, 50 mM of ascorbic acid, 10 À8 M of dexamethasone and 10 ng/ml of TGF-b1, as detailed elsewhere. 27 To induce calcification, pellets were then cultured in a-MEM containing 5% FCS, 10 mg/ml of insulin, 10 À8 M 1,25 (OH) 2 VD 3 and 5 mM b-GP. Pellets were finally treated on day 24 with 1 ng/ml of TNF-a and 0.1 ng/ml of IL-1b for 2 days for PCR analysis or 7 days to assess TNAP activity.…”
Section: Cell Culturesmentioning
confidence: 99%
“…They also reported that autologous pericranial graft resurfacing was performed after condylectomy and discectomy, and showed regenerated condyle with hyaline cartilage; they concluded that pericranial grafts controlled oxygen tension in the TMj. relatively low oxygen tension favors differentiation into cartilage cells, which occurs on the articular surface [10]. Fujita et al [6] reported that mesenchymal cell aggregation in the resection area was confirmed in the early stage of condylar regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Low oxygen levels have been reported to be a more potent promoter of chondrogenesis than dynamic compression (Meyer et al, 2010). Previous studies have shown controversial findings in relation to the effect of oxygen tension on chondrogenic differentiation of mesenchymal stem cells with some reporting increased proliferation rates and chondrogenic potency and others reporting reduced proliferation and differentiation potency (Grayson et al, 2007;Merceron et al, 2010;Krinner et al, 2009;Holzwarth et al, 2010). …”
Section: Mechanical Stimuli and Bioreactorsmentioning
confidence: 99%